2020
DOI: 10.1590/1806-93042020000400013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with group B streptococcal colonization in pregnant women

Abstract: Objectives: to estimate the prevalence and the factors associated with the colonization by group B streptococcus (GBS) in pregnant women from the urban area attended at health units in a municipality in northeastern Brazil. Methods: it is a cross-sectional study conducted from January 2017 to March 2018. Vagino-rectal swabs were collected from 210 pregnant women between 32 and 40 weeks of gestation. The swabs were seeded on 5% sheep blood agar and on chromogenic agar. For confirmatory identification of GBS, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Low weight during pregnancy was significantly associated with the occurrence of anemia when the CDC criterion was adopted, which corroborates findings from previous studies carried out in Maceió, which identified an association between anemia and insufficient gestational weight gain and low weight. 20 As such a feature in non-pregnant women of childbearing age also entails a greater risk of anemia, 18 both disorders actually seem to represent "baseline issues" that become aggravated by pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Low weight during pregnancy was significantly associated with the occurrence of anemia when the CDC criterion was adopted, which corroborates findings from previous studies carried out in Maceió, which identified an association between anemia and insufficient gestational weight gain and low weight. 20 As such a feature in non-pregnant women of childbearing age also entails a greater risk of anemia, 18 both disorders actually seem to represent "baseline issues" that become aggravated by pregnancy.…”
Section: Discussionmentioning
confidence: 99%